BIRDS. - Mohamad Fizl Sidq, Ramji; Nurul Ashikeen, Ab Razak; Ivana Berlinda, Bilang; Rahah, Mohd Yakup; Isa, Sait; Badiozaman, Sulaiman (UNIMAS Publisher and Natural History Publications (Borneo) Sdn. Bhd., 2023)
Bako National Park is the oldest protected area in Sarawak, being gazetted on 1 May 1957. It has a total size of 2,727 ha and is situated at the tip of the Muara Tebas Peninsula. The Park has a fascinating diversity of habitats, which includes Kerangas forest, beach vegetation, grasslands, mangroves, as well as mixed dipterocarp and peat swamp forests. Several jungle trails (Tanjung Sapi, Telok Paku, Ulu Assam, Telok Delima, Serait, Telok Pandan Kecil, Telok Pandan Besar, Lintang, Tajor, Ulu Serait, Bukit Gendol, Paya Jelutong, Bukit Keruing, Telok Sibur, Telok Limau, and Telok Keruin) traverse these forests and provides excellent opportunity for nature lovers to explore and observe wildlife in a natural setting.